An injectable and physical levan-based hydrogel as a dermal filler for soft tissue augmentation. (15th August 2018) - Choi, Won Il; Hwang, Youngmin; Sahu, Abhishek; Min, Kiyoon; Sung, Daekyung; Tae, Giyoong; Chang, Jeong Ho
Abstract : A novel levan-based injectable hydrogel was developed as a dermal filler having better in vivo stability and efficacy compared to HA-based hydrogel. Abstract : The use of injectable materials as a biofiller for soft tissue augmentation has been increasing worldwide. Levan is a biocompatible and inexpensive polysaccharide with great potential in biomaterial applications, but it has not been extensively studied. In this study, we evaluated the potential of levan as a new material for dermal fillers and prepared an injectable and physical levan-based hydrogel by combining levan with Pluronic and carboxymethyl cellulose (CMC). A sol state was prepared by mixing the polymers in a specific ratio at 4 °C for 2 days and the hydrogel was formed by increasing the temperature to 37 °C. The elastic modulus of the levan hydrogel was higher than that of a hyaluronic acid (HA)-based hydrogel. The SEM images of the levan hydrogel showed an interconnected porous structure, similar to the HA hydrogel. Levan showed non-cytotoxicity, enhanced cell proliferation, and higher amount of collagen synthesis in human dermal fibroblast cells compared to HA. The injected levan hydrogel was biocompatible and stable over 2 weeks in vivo, longer than the Pluronic F127 hydrogel or HA hydrogel. Also, the levan hydrogel showed a higher amount of collagen production than the HA hydrogel in vivo . More importantly, the levan hydrogel showed enhanced anti-wrinkle efficacy compared to the HA hydrogel in a wrinkle model mouse. Thus, the levan hydrogel with injectability, biocompatibility, and an anti-wrinkle effect has high potential as an alternative to existing commercial dermal fillers.